Comparison between galvanic sensors (steel/stainless steel) and half cell potentials (Ecorr) for monitoring the corrosion risk of steel reinforcement in concrete structures - Pérez DíazJosé Luis; Cabrera Madrid, Jesús Alejandro; Hernández Cruz, Daniel; Godínez Domínguez, Eber Alberto; Mundo Molina, Martín Dagoberto (Revista ALCONPAT, 2022)
The corrosion risk of steel in concrete was assessed using internal galvanic carbon/stainless steel sensors and the external Cu/CuSO4 electrode. The sensors were used to monitor the macrocell potentials and currents of reinforced concrete prismatic specimens, with water to cement ratios of 0.4 and 0.6, immersed in 5% NaCl solution, for 18 months. The results of the potentials showed a good correlation between the two reference electrodes, being able to evaluate the corrosion of the system. In addition, the electrochemical noise technique supports observations of the effect of chloride ions. Therefore, galvanic sensors can be considered for implementation in the monitoring and evaluation of corrosion risk of reinforced concrete structures.